Production of renewable fuel and value-added bioproducts using pineapple leaves in Costa Rica - Chen, Ana (2020)
Pineapple, Ananas comosus, is one of the most important cash crops in Costa Rica with more than 44,500 ha of plantation. The pineapple industry contributes approximately 1.7% of the gross domestic product (GDP) of Costa Rica. Pineapple cultivation generates a large amount of plant residues (250 metric tons per hectare of wet plant residues mainly leaves). Current practices of the field residue handing include direct burning, in situ decomposition and removal of residue before planting, which are neither economically sound nor environmentally friendly. New approaches are urgently needed to utilize the residues and improve sustainability of pineapple production in Costa Rica. This study developed a simple, efficient process to convert the pineapple plant leaves into bioethanol, spent yeast proteins, and fibrous material (pulp). The residue was first treated by a mechanical extruder to generate juice and fibrous material. The juice was fermented by a yeast, Kluyveromyces marxianus, to produce ethanol and spent yeast proteins. Under the selected process conditions, the plant leaves (125 tons fresh weight per year) from 1 ha can generate 2.1 tons of bio-ethanol, 1.55 tons of spent yeast biomass, and 11.65 tons of dry fibrous material. The mass and energy balance analysis concluded that using the studied process, the pineapple plant leaves from 44,500 ha of pineapple plantation in Costa Rica can produce 93,043, 68,975, and 518,425 tons of bioethanol, spent yeast, and fibrous material per year, respectively. The amount of bioethanol is able to replace approximately 8.51% of transportation fossil fuel consumption in Costa Rica.